Nonmagnetic and Magnetic Quantum Dots - Stavrou, Vasilios N. (IntechOpen, 2018)
The book entitled Nonmagnetic and Magnetic Quantum Dots is divided into two sections. In Section 1, the chapters are related to nonmagnetic quantum dots and their applications. More specifically, exact models and numerical methods have been presented to describe the analytical solution of the carrier wave functions, the quantum mechanical aspects of quantum dots, and the comparison of the latter to experimental data. Furthermore, methods to produce quantum dots, synthesis techniques of colloidal quantum dots, and applications on sensors and biology, among others, are included in this section. In Section 2, a few topics of magnetic quantum dots and their applications are presented. The section starts with a theoretical model to describe the magnetization dynamics in magnetic quantum dot array and the description of dilute magnetic semiconducting quantum dots and their applications. Additionally, a few applications of magnetic quantum dots in sensors, biology, and medicine are included in Section 2.